Newborn Car Bed Testing in a Community Hospital: Implementing the American Academy of Pediatrics Recommendations - Wilker, Richard E.; Cotoni, Brenda J.; Mirando, Carolyn S.; Bass, Joel L. (American Journal of Perinatology, 2014)
Objective This study was designed to describe our experience in implementing the American Academy of Pediatrics (AAP) recommendation to test infants in a car bed if they fail a car seat challenge test.Study Design Car seat challenge testing was performed for 90 minutes or the anticipated duration of the trip home, whichever was longer. Based on the pulse oximetry saturation values (90–92% or < 90%) two categories of test failure were used. Infants who failed in the car seat were tested in the car bed. Testing took place in both the normal newborn nursery (NBN) and special care nursery (SCN). NBN babies who failed in the car bed were transferred to our SCN for additional assessment and management.Results A total of 197 infants were tested in car seats out of which 177 (89.8%) passed the test. Of the 20 infants who failed, 16 passed the car bed challenge test on the first attempt and were discharged in those devices. All infants who failed the car bed challenge were NBN patients.Conclusions Using 93% as the acceptable lower limit of oxygenation we successfully implemented the AAP recommendations for car bed challenge testing in our nursery.
Keywords: car seats; car beds; oxygen desaturation; apnea; bradycardia